1993
DOI: 10.1007/bf00314554
|View full text |Cite
|
Sign up to set email alerts
|

In vivo secretory responses of submandibular glands in streptozotocin-diabetic rats to sympathetic and parasympathetic nerve stimulation

Abstract: Submandibular gland responses to sympathetic and parasympathetic nerve stimulation were studied in streptozotocin-diabetic rats. Morphologically, the acinar cells in control glands were relatively uniform in size and contained electron-lucent granules. The granular ducts were distinguished by the presence of electron-dense granules. With the exception of intracellular lipid droplets and the presence of a few autophagosomes in diabetic glands, no consistent differences in acinar cell structure were observed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
5
0
10
Order By: Relevance
“…Related studies [23][24][25][26][27] showed that, in diabetes-induced rat submandibular glands, the secretion material accumulate in acinar cells' cytoplasm, resulting in degenerative changes followed by cell death. In late-phase diabetes, an increase in the number of autophagic structures occurs in granular duct cells.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies [23][24][25][26][27] showed that, in diabetes-induced rat submandibular glands, the secretion material accumulate in acinar cells' cytoplasm, resulting in degenerative changes followed by cell death. In late-phase diabetes, an increase in the number of autophagic structures occurs in granular duct cells.…”
Section: Discussionmentioning
confidence: 99%
“…Os sintomas clássicos do diabetes incluem poliúria, polidipsia, perda de peso, às vezes polifagia e visão embaçada (KUZUYA et al, 2002), em nosso estudo os ratos diabéticos perderam peso, ingeriram mais líquido (polidipsia) e alimento (polifagia). A polifagia em ratos já foi relatada por outros autores (BARBERA et al, 2001; BARBERA; RODRIGUEZ-GIL; GUINOVART, 1994;GIRON et al, 2003), porém outros não observaram polifagia entre os animais diabéticos (ANDERSON et al, 1993;BARBERA et al, 1997;NICOLAU et al, 2005). A glicemia inicial e final dos animais diabéticos que participaram desse estudo foi acima de 250mg/dl de sangue e a glicemia final mostrou que os grupos alimentados, controle e diabético, apresentam glicemia superior aos grupos em jejum.…”
Section: Discussionunclassified
“…A dificuldade de a glicose ser transportada para dentro da célula prejudica o anabolismo e favorece o catabolismo, desta forma é comum os portadores de diabete perderem peso corporal, assim como a redução de peso dos tecidos periféricos como as glândulas salivares (ANDERSON, 1983;ANDERSON et al, 1993;ANDERSON et al, 1989;MAHAY et al, 2004 VAN VENROOIJ, 1975). Na glândula P a amilase é a proteína secretada em maior quantidade, em ratos diabéticos tanto a concentração de amilase quanto a síntese de RNAm estão reduzidas (KIM et al, 1990;SZCZEPANSKI;MEDNIEKS;HAND, 1998), embora outros autores não tenham encontrado alteração na concentração de amilase em rato diabéticos (NEWRICK et al, 1991).…”
Section: Discussionunclassified
See 2 more Smart Citations